Patterns of inappropriate use of meropenem as antibacterial - Atalah Hussin, Nadia; Atalah Hussin, Ali (Tikrit Journal of Pharmaceutical Sciences, 2023)
Introduction: The development of antibiotic resistant organisms is related to inappropriate use of antibiotics, especially in developing countries where broad spectrum antibiotics can be purchased without prescription. Some of the common causes that contribute to the development of antimicrobial resistance are unnecessary use of antimicrobial drugs, inappropriate dose, inadequate duration of therapy. The aim of the study: The present study aiming to focus light on the inappropriate use of meropenem a lone, as it is one of the preserved last choices of antibiotics and is under restricted regulations for description and dispensing by ministry of health in Iraq. Materials and methods: This study was carried out in Tertiary –care hospital. Hundred and thirty patients received meropenem had included in this study. The meropenem administration was followed up regarding dose, frequency, duration, indication. The bacteria were isolated and identified by standard conventional methods in addition to Api20E systems. Antibiotic sensitivity testing carried out by Kirby-Bauer disc diffusion method. The result: Collectively 54% of the patients included in this study recieved meropenem inappropriately. The antibiotics sensitivity test by the hospital was inadequate. The most common bacteria isolated from the study were gram negative bacteria (72.7%). E.coli was the most predominant isolated bacteria (32%). Conclusion: The abuse of antibiotics is very common especially because antibiotic sensitivity test is almost neglected in Iraq. Fundamental changes are required to solve this problem. For the future of the next generations let us start a new policy in prescribing and dispensing antibiotics in Iraq